ENTERPRISE ARCHITECTURE FOR BANKING IN THE INDUSTRIAL REVOLUTION ERA 4.0 - Firman Pradana Rachman; Eko Indrajid; Erick Dazki (UNIVERSITAS PAKUAN, 2022)
The banking industry must keep up with the latest technological developments. If not, the banking industry will start to be abandoned by customers. This study presents enterprise architecture recommendations for the banking industry in the era of the industrial revolution 4.0. The architecture contained in this research consists of business architecture, information systems architecture, application architecture and technology architecture. The hope is that with the recommended architecture, we can adopt the latest technology and the banking industry can still compete in the midst of change.